ON THE FEATURES OF FUNCTIONING OF LOCAL REFERENCE PREVERBS IN WEST-CAUCASIAN LANGUAGES - A. V. Avidzba (Гуманитарные и юридические исследования)
In West-Caucasian languages the location and the direction of an action are expressed morphologically. The article considers the characteristic features of preverbs of local reference in these languages. Similar and distinctive features of usage of local preverbs among the languages are analysed at different levels: chronological, structural, phonetic, grammatical. The existing research findings are taken into account, a rather wide practical material is given.